Pembentukan Karakter Demokratis Anak Melalui Tradisi Markobar - Hamdi Abdullah Hasibuan; Nadila Sari (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
This study is based on the formation of democratic character that always takes place in schools. The formation of democratic character can also be carried out in the family and community through the markobar tradition. Markobar is a tradition that involves family members and the family system in the Mandailing community. Markobar is a tradition that is carried out by giving opinions and ideas in turn. This study aims to examine more deeply the process of forming a democratic character through the Markobar tradition. The study used the first data source, namely the literature. The literature is the first source used, such as books, journals, magazines, sources of printed library materials, and relevant previous research results. The data collection technique used is a qualitative data collection technique that includes a literature study. Then, data analysis was carried out using data reduction, data display, verification, and concluding. This study found that the formation of democratic character can occur within the family and community through the Markobar tradition. The Markobar tradition is a medium that trains children to be democratic, to respect opinions, and differences, and to uphold the rights of everyone. In the process of forming democratic character in the family and society, patterns of formation are found, namely habituation, exemplary, ongoing, and involving family members. The formation of a child's democratic character occurs along with ongoing interactions and actions in the family and community